Quinine Esterswith 1,2-Azole, Pyridine and Adamantane Fragments - Mukusheva, G.K.; Zhasymbekova, A.R.; Seidakhmetova, R.B.; Nurkenov, O.A.; Akishina, E.A.; Petkevich, S.K.; Dikusar, E.A.; Potkin, V.I. (Molecules, 2022)
An efficient method of producing quinine derivatives via reaction of acylation with 4,5-dichloroisothiazole-3-, 5-arylisoxazole-3-, adamantane- and hydrochlorides of pyridine-3- and pyridine-4-carbonyl chlorides was developed. All synthesized compounds were tested for antiviral, antimicrobial and analgesic activity. The most pronounced antibacterial activity was shown by the compounds 2e, 3b, 3c and 3e with isoxazole and pyridine fragments. It was found that most of the tested compounds showed significant analgesic activity reducing the pain response of animals to the irritating effect of acetic acid.
Keywords: quinine; esters; isoxazole; isothiazole; pyridine; adamantane; quaternary pyridinium salts; antiviral activity; antimicrobial activity; analgesic activity